A short guide to college writing - Barnet, Sylvan; Bellanca, Pat; Stubbs, Marcia (Boston, Massachusetts : Pearson, 2013)
One of the high-quality, low-priced entries in Longman's Penguin Academics Series, "A Short Guide to College Writing" is a clear and authoritative brief rhetoric that emphasizes analysis, argument, and research in academic writing
1. Developing ideas -- 2. Drafting and revising -- 3. Shaping paragraphs -- 4. Revising for conciseness -- 5. Revising for clarity -- 6. Writing with style -- 7. Using sources -- 8. Analyzing texts -- 9. Persuading readers -- 10. Writing the research essay -- 11. Punctuating sentences -- 12. Using the right word -- 13. Documenting sources --14. Preparing the manuscript
Includes bibliographical references and index
Keywords: English language -- Rhetoric -- Handbooks, manuals, etc; Report writing -- Handbooks, manuals, etc